Cyber-Transcendence and Immanence as a Religio-Spiritual Phenomenon in Cyberpunk Anime - Frey, Malte (Journal for Religion, Film and Media, 2023)
This article argues that Western cyberpunk narratives often suggest a technologically invoked transcendence, a cyber-transcendence, which represents a new ontological sphere and offers catharsis in dystopian scenarios. While Japanese cyberpunk anime also explore the idea of cyber-transcendence, the clear distinction between immanence and transcendence often becomes blurred. Aesthetic concepts invoking transcendence can be linked to the awe-inspiring kami (deities) of Japanese Shinto, which are intertwined with the immanent sphere of reality rather than external to it. In Western cyberpunk, cyber-transcendence seems to provide the sense of depth that Paul Tillich labels the “dimension of religion”, in contrast to postmodernist meaninglessness. Cyberpunk anime provide an understanding of transcendence as a religious dimension that exists within reality.